Histone Acetylation Modifiers in the Pathogenesis of Alzheimer’s Disease - Lu, Xi; Wang, Li; Yu, Caijia; Yu, Daohai; Yu, Gang (Frontiers in Cellular Neuroscience, 2015)
It is becoming more evident that histone acetylation, as one of the epigenetic modifications or markers, plays a key role in the etiology of Alzheimer’s disease (AD). Histone acetylases (HATs) and histone deacetylases (HDACs) are the well-known covalent enzymes that modify the reversible acetylation of lysine residues in histone amino-terminal domains. In AD, however, the roles of these enzymes are controversial. Some recent studies indicate that HDAChistone deacetylases inhibitors are neuroprotective by regulating memory and synaptic dysfunctions deficit in cellular and animal models of AD, while on the other hand, increases in histone acetylation have been implicated in AD pathology. In this review, we focus on the recent advances on the roles of histone acetylation covalent enzymes in AD and discuss how targeting these enzymes can ultimately lead to therapeutic approaches for treating AD.